Targeting CD4+ T cells through gut microbiota: therapeutic potential of traditional Chinese medicine in inflammatory bowel disease - Xingyao Lu; Yichuan Xv; Weiye Hu; Boyun Sun; Hongyi Hu (Frontiers in Cellular and Infection Microbiology)
Inflammatory Bowel Disease (IBD) is an autoimmune disease characterized by chronic relapsing inflammation of the intestinal tract. Gut microbiota (GM) and CD4+T cells are important in the development of IBD. A lot of studies have shown that GM and their metabolites like short-chain fatty acids, bile acids and tryptophan can be involved in the differentiation of CD4+T cells through various mechanisms, which in turn regulate the immune homeostasis of the IBD patients. Therefore, regulating CD4+T cells through GM may be a potential therapeutic direction for the treatment of IBD. Many studies have shown that Traditional Chinese Medicine (TCM) formulas and some herbal extracts can affect CD4+T cell differentiation by regulating GM and its metabolites. In this review, we mainly focus on the role of GM and their metabolites in regulating the differentiation of CD4+T cells and their correlation with IBD. We also summarize the current research progress on the regulation of this process by TCM.